Recognition, Regulation, Revitalisation Place Names and Indigenous Languages - Loth, Chrismi-Rinda (Proceedings of the 5th International Symposium on Place Names 2019, 2020)
Recognition, Regulation, Revitalisation: Place Names and Indigenous Languages is a selection of double-blind peer-reviewed papers from the 5th International Symposium on Place Names that took place 18-20 September 2020 in Clarens, South Africa. The symposium celebrated 2019 as the International Year of Indigenous Languages as declared by the United Nations.